2017
DOI: 10.1093/nar/gkx1195
|View full text |Cite
|
Sign up to set email alerts
|

PaSD-qc: quality control for single cell whole-genome sequencing data using power spectral density estimation

Abstract: Single cell whole-genome sequencing (scWGS) is providing novel insights into the nature of genetic heterogeneity in normal and diseased cells. However, the whole-genome amplification process required for scWGS introduces biases into the resulting sequencing that can confound downstream analysis. Here, we present a statistical method, with an accompanying package PaSD-qc (Power Spectral Density-qc), that evaluates the properties and quality of single cell libraries. It uses a modified power spectral density to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Phasing was performed on the GATK HaplotypeCaller germline variants from replicate 6 bulk brain tissue using Eagle [ 49 ] and the 1000 Genomes Phase 3 reference panel [ 50 ]. Second, we determined the optimal kernel size to maximize accuracy using PaSD-qc [ 51 ], which was determined to be 10 kb. Third, we instituted a likelihood ratio test to distinguish a first-round amplification artifact from a true mosaic variant; let f ( X ; p ) be the probability of observing reads X where p is the expected proportion of alternate reads.…”
Section: Methodsmentioning
confidence: 99%
“…Phasing was performed on the GATK HaplotypeCaller germline variants from replicate 6 bulk brain tissue using Eagle [ 49 ] and the 1000 Genomes Phase 3 reference panel [ 50 ]. Second, we determined the optimal kernel size to maximize accuracy using PaSD-qc [ 51 ], which was determined to be 10 kb. Third, we instituted a likelihood ratio test to distinguish a first-round amplification artifact from a true mosaic variant; let f ( X ; p ) be the probability of observing reads X where p is the expected proportion of alternate reads.…”
Section: Methodsmentioning
confidence: 99%
“…Information on haplotype phase will also be useful for calling retrotranspon insertions ( Evrony et al , 2012 ) or single-nucleotide variants (SNVs). Recently, ( Bohrson et al , 2018 ) showed how they were able to reduce false positive rates in SNV calling in single-cell DNA sequencing by phasing SNVs to nearby SNPs. However, many SNVs cannot be phased to SNPs with short reads, especially in whole-exome data.…”
Section: Discussionmentioning
confidence: 99%
“…Since each read generally derives from a single chromosome, if a read spans multiple SNPs, then the observed alleles are presumed from a single haplotype. Haplotype and SNP phase information has applications in population genetics ( Tewhey et al , 2011 ) and clinical and medical genomics ( Glusman et al , 2014 ; Roach et al , 2010 ; van de Ven et al , 2012 ) as well as being used to improve other analyses such as SNP imputation and genotyping ( Browning and Yu, 2009 ; Marchini et al , 2007 ) and somatic variant calling ( Bohrson et al , 2018 ). Obtaining long continuous haplotype blocks is a challenge as the distance between adjacent SNPs is longer than reads and read fragments in most sequencing technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Phasing was performed on the GATK HaplotypeCaller germline variants from Replicate 6 bulk brain tissue using Eagle 46 and the 1000 Genomes Phase 3 reference panel 47 . Second, we determined the optimal kernel size to maximize accuracy using PaSD-qc 48 , which was determined to be 10 kb. Third, we instituted a likelihood ratio test to distinguish a first-round amplification artefact from a true mosaic variant; let f(X;p ) be the probability of observing reads X where p is the expected proportion of alternate reads.…”
Section: Methodsmentioning
confidence: 99%